International Trade, Information and Communication Technology, and the Covid-19 Pandemic: Indonesian Empirical Evidence - Belantika, Bernica Tiyas; Kartiasih, Fitri (Indonesian Journal of Economics and Management, 2024)
Information and communication technology (ICT) innovations play an important role in helping poor and developing countries improve their trade relations with other countries. In Indonesia, the information and communication sector is one of the contributing sectors to gross domestic product, which grew positively among the six other sectors during the Covid-19 pandemic, while other sectors experienced contractions. The impact of the Covid-19 pandemic has limited economic activity, one of which is international trade. ICT can be an alternative solution to Indonesia's decline in international trade. This study aims to analyze the influence of ICT and the Covid-19 pandemic on Indonesia's exports and imports with the 14 largest trading partner countries in 2005–2021 using the gravity model in the data panel. The results showed that percentage of individuals using internet in trading partner countries and the number of mobile cellular subscriptions in Indonesia and trading partner countries significantly increased the value of Indonesia’s export. Meanwhile, the percentage of individuals using internet in trading partner countries and the number of mobile cellular subscriptions in Indonesia significantly increased the value of Indonesia's imports. ICT has a large role, so that the influence of the Covid-19 pandemic is only temporary and does not significantly affect international trade.